THE EFFECT OF CUSTOMER AMOUNT, WATER LOSS RATE, OPERATING EXPENSES ON RENTABILITY OF PDAM IN YOGYAKARTA - Sabilla, Gervy; Natasari, Dina (J-ISCAN: Journal of Islamic Accounting Research, 2024)
Public sector financial management is important for Perumda PDAM in running its business. The main issue in optimizing financial performance is something that needs to be faced by companies today. The assessment of financial performance is measured through ROE indicators. This study aims to determine the effect of the number of customers, the level of water loss, and operational expenses on profitability at PDAMs in DIY Province. The dependent variable in this study is return on equity (ROE). The independent variable consists of three variables, namely the number of customers, the level of water loss, and operational expenses. The research population is all PDAM Regional Public Companies in Indonesia for the period 2017 - 2022. The research sample amounted to five PDAM Perumda that met the research criteria. The data testing method uses multiple linear regression analysis. The test results concluded that partially only the variable number of customers and the level of water loss had a significant effect on profitability as measured by the ROE indicator. However, based on the results of the F statistical test, it is concluded that the variables of the number of customers, the level of water loss, and operational expenses have a significant influence simultaneously on the profitability of PDAMs.